Dimensi Kekuasaan Politik Berasaskan Ketuhanan Yang Maha Esa - Ritaudin, M. Sidi (Jurnal Review Politik, 2019)
This article aims to find out how the dimension of political power in the unitary state of the Republic of Indonesia which is based on the Godhead, which has not been known whether the administration of the state is really based on the Godhead, because after the 1998 reforms, with the abolition of P-4 lessons in schools and education begin to recognize the values ??of Pancasila and are ignorant of being aware of this, and the government has begun promoting the 4 pillars of nationhood. The Divine Principle in the sense of a divinity that is cultured, spacious and tolerant; not the God who attacks each other, damaging and isolating. Humanitarian Principle: that which is humanity and justice; not colonizing and exploitative. Nationality Principle: that is able to develop unity of various differences, "unity in diversity"; not nationality that negates differences or rejects unity. Democratic Principles: i.e. developing consensus agreement; not a democracy dictated by a majority vote (majorocracy) or a minority of ruling-financiers (minorocracy) elites. The Principle of Welfare: namely developing participation and emancipation in the economic field with a family spirit; not a welfare vision based on individualism-capitalism; This is the concern of the discussion.